2008
DOI: 10.1103/physrevb.78.115102
|View full text |Cite
|
Sign up to set email alerts
|

Sum rules and bath parametrization for quantum cluster theories

Abstract: We analyze cellular dynamical mean-field theory ͑CDMFT͒ and the dynamical cluster approximation ͑DCA͒. We derive exact sum-rules for the hybridization functions and give examples for dynamical mean-field theory, CDMFT, and DCA. For impurity solvers based on a Hamiltonian, these sum rules can be used to monitor convergence of the bath-parametrization. We further discuss how the symmetry of the cluster naturally leads to a decomposition of the bath Green matrix into irreducible components, which can be parametri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
105
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(110 citation statements)
references
References 44 publications
4
105
0
Order By: Relevance
“…In low-dimensional systems (single site) DMFT is in general not a good approximation. In particular, for the one-dimensional Hubbard model non-local correlations are in fact dominant 14 , leading to a complete breakdown of Fermi liquid physics and the formation of a novel low-energy fixed point, the Luttinger liquid 4 . Similarly, in two dimensions a strong influence of spin-fluctuations in the Hubbard model is expected, in particular at and close to half filling.…”
mentioning
confidence: 99%
“…In low-dimensional systems (single site) DMFT is in general not a good approximation. In particular, for the one-dimensional Hubbard model non-local correlations are in fact dominant 14 , leading to a complete breakdown of Fermi liquid physics and the formation of a novel low-energy fixed point, the Luttinger liquid 4 . Similarly, in two dimensions a strong influence of spin-fluctuations in the Hubbard model is expected, in particular at and close to half filling.…”
mentioning
confidence: 99%
“…In the case of an isotropic triangular lattice, Green's function and self-energy can be diagonalized by an analogous transformation to molecular orbitals appropriate for a three-site cluster. 45 The question then arises whether these cluster molecular orbitals in the single-band case obey a similar scenario as the multiorbital systems mentioned above.…”
Section: Introductionmentioning
confidence: 99%
“…The pioneering work of Huscroft et al [22] showed the existence of a normal-state pseudogap in the dynamical mean field approximation and many authors (using mainly N = 4 approximations) have studied its properties [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] and several groups (still within the 4-site approximation) have studied the interplay of superconductivity and the pseudogap [31,[42][43][44][45][46]. A key finding of the 4-site work, in contrast to the larger-cluster studies of Ref.…”
mentioning
confidence: 99%